Control of conventionality and judicial decisions - Tucto Livia, Eloisa (2024)
The American Convention on Human Rights, also known as the Pact of San José, Costa Rica, was recognized on November 22, 1969 in that city at the Inter-American Specialized Conference on Human Rights. It entered into force on July 18, 1978, following the deposit of the eleventh instrument of ratification by a Member State of the Organization of American States (OAS), in accordance with Article 74.2 thereof. It was signed by our country on July 27, 1977 and approved by Decree Law No. 22231 on July 11, 1978. The Convention created two competent bodies to address human rights violations: the Inter-American Commission on Human Rights (IACHR) and the Inter-American Court of Human Rights (IACHR Court). The former is a principal, autonomous body of the OAS charged with promoting and safeguarding human rights in the Americas; it is based in Washington, D.C. The latter is a regional body for the protection of human rights. The second is a regional human rights protection body with a judicial character, i.e., it is an inter-American court of justice in human rights matters, like the European Court and the African Court of Human Rights. In this regard, the “Court has jurisdiction to hear any case concerning the interpretation and application of the provisions of this Convention that is submitted to it, provided that the States parties to the case have recognized and acknowledge such jurisdiction [...]” (Article 62.3), its other competencies are set forth in Articles 63 and 64 of the Convention.